Biological effects of blocking blue and other visible light on the mouse retina. (4th December 2013) - Narimatsu, Toshio; Ozawa, Yoko; Miyake, Seiji; Kubota, Shunsuke; Yuki, Kenya; Nagai, Norihiro; Tsubota, Kazuo
Abstract Background To elucidate the biological effects of blocking fluorescent light on the retina using specific blocking materials. Methods Seven‐ to 8‐week‐old BALB/c mice were divided into three groups and placed in one of the three boxes: one blocked ultraviolet and violet wavelengths of light (violet blockade), one blocked ultraviolet, violet, blue and some other visible wavelengths (blue‐plus blockade), and one allowed most visible light to pass through (control). They were then exposed to a white fluorescent lamp for 1 h at 5.65E‐05 mW/cm2/s. After treatment, the electroretinogram, retinal outer nuclear layer thickness and retinal outer segment length were measured. In addition, retinal apoptotic cells were quantified by TdT‐mediated dUTP nick‐end labelling assay and c‐Fos messenger RNA, and protein levels were measured by real‐time reverse‐transcription polymerase chain reaction and immunoblot analyses, respectively. Results The blue‐plus blockade group retained a significantly better electroretinogram response following light exposure than the control or violet blockade groups. The blue‐plus blockade group also exhibited greater outer nuclear layer thickness and greater outer‐segment length, and fewer apoptotic cells after light exposure than the other groups. The c‐Fos messenger RNA and protein levels were substantially reduced in the blue‐plus blockade group and reduced to a lesser extent in the violet blockade group. Conclusions The blockade of blue plus additional visible wavelengths of light was most effective in protecting the retina from light‐induced damage. The blockade of violet light alone was also effective in reducing intracellular molecular responses, but these effects were not sufficient for attenuating retinal degeneration.